1987
DOI: 10.1002/app.1987.070340811
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior of polybutene‐1 in the anisotropic system blended with polypropylene

Abstract: SynopsisDevelopment of supermolecular structure in drawn polypropylene (PP)/polybutene-1 (PB-1) blends was studied. PP (matrix)/PB-1 (70/30) blend films were drawn and heat-treated at fixed length or free ends at temperatures above the melting point of PB-1. It was found that a long axis of the PB-1 lamella is aligned perpendicular to the draw direction, and the c-axis of the PB-1 crystal is oriented perpendicular both to the draw direction and the plane of the surface of the blend film. Drawn, then heat-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…In many cases of bulk crystallization of polymers, when the nucleation takes place preferentially at the surface of a heterogeneous domain present in the molten system, the crystallization of the polymer component concerned would be usually accelerated, often attended by lowering of the growth dimension. [17,18] In the present case of the graft copolymers, however, the crystallization rate of the PCL component was generally suppressed, compared with that of ungrafted PCL; besides we observed a slower growth as ''spherulite'' of the crystal for any composition of the CA-and CB-series investigated, as the optical evidence is shown later. From these considerations and the finding of seriously reduced n values even for the CB-g-PCL samples composed of a miscible polymer pair, it seems natural to simply assume that the major factor responsible to the diminution of the kinetic parameter is the extremely slower diffusion of PCL chains due to the anchoring onto the semi-rigid cellulosic backbone.…”
Section: Quantitative Analysis Of Isothermal Crystallization Behaviorsupporting
confidence: 58%
“…In many cases of bulk crystallization of polymers, when the nucleation takes place preferentially at the surface of a heterogeneous domain present in the molten system, the crystallization of the polymer component concerned would be usually accelerated, often attended by lowering of the growth dimension. [17,18] In the present case of the graft copolymers, however, the crystallization rate of the PCL component was generally suppressed, compared with that of ungrafted PCL; besides we observed a slower growth as ''spherulite'' of the crystal for any composition of the CA-and CB-series investigated, as the optical evidence is shown later. From these considerations and the finding of seriously reduced n values even for the CB-g-PCL samples composed of a miscible polymer pair, it seems natural to simply assume that the major factor responsible to the diminution of the kinetic parameter is the extremely slower diffusion of PCL chains due to the anchoring onto the semi-rigid cellulosic backbone.…”
Section: Quantitative Analysis Of Isothermal Crystallization Behaviorsupporting
confidence: 58%
“…A number of studies have been reported on the oriented crystallization of immiscible, but mechanically compatible, polymer blends consisting of two crystalline polymers, such as poly(propylene) (PP)/polyethylene (PE), [7][8][9] PP/ isotactic poly(butene-1), [10] PP/polyamide 11, [11] polyethylene glycol (PEG)/polyamide, [12] PCL/PE, [13] and poly(vinylidene fluoride)/polyamide 11. [14,15] If a component with a lower melting temperature is crystallized in the oriented matrix of another component with a higher melting temperature, some unusual orientation textures, such as orthogonal orientation, [8,10,11,14,15] or tilted orientation, [7][8][9]11] are induced in the dispersed phase.…”
Section: Full Papermentioning
confidence: 99%
“…[14,15] If a component with a lower melting temperature is crystallized in the oriented matrix of another component with a higher melting temperature, some unusual orientation textures, such as orthogonal orientation, [8,10,11,14,15] or tilted orientation, [7][8][9]11] are induced in the dispersed phase. The unique orientation behaviors have been explained either by epitaxial crystal growth on the polymer crystal, [11][12][13] thermal shrinkage stress, [7] or transcrystallization.…”
Section: Full Papermentioning
confidence: 99%
See 2 more Smart Citations